Вольт-амперные характеристики наноразмерных пленок оксида титана, полученных анодным окислением - Коваленко, Д. А.; Буневич, М. А.; Горбачев, Д. В.; Врублевский, И. А. (БНТУ, 2025)
This work studies the electrical properties of nanoscale TiO₂ films obtained by anodic oxidation. Current-voltage characteristics measured in the temperature range 263–300 K show a dominant charge injection mechanism at the metal-oxide interface. The analysis confirms that the conductivity is determined by defect states rather than the intrinsic properties of the dielectric.